Spouse-Appraised Memory Functioning Predicts Memory Decline Better Than Subjective Memory Complaints in Community Dwelling Older Adults at Genetic Risk for Alzheimer's Disease - Bellaali, Youssef; Woodard, John L.; Hanseeuw, Bernard; Ivanoiu, Adrian (Frontiers in Psychiatry, 2021)
Objective: Alzheimer's disease (AD) begins with subtle memory decline, years before dementia onset. The presence of subjective memory complaints (SMC) has been proposed as a marker of preclinical AD. However, recent evidence has demonstrated early and progressive loss of awareness of memory difficulties in non-demented older adults harboring AD pathology. We investigated the respective contributions of SMC and spouse-appraised memory functioning (SAM) to predict memory decline in a large cohort of non-demented older adults. Methods: The Wisconsin Longitudinal Study collected cognitive data from a community-based cohort of 3,583 participants in both 2005 and 2011. The participant and the participant’s spouse were each asked to rate the participant’s memory functioning using a Likert scale. We predicted change in objective episodic memory with models including baseline SMC, baseline SAM, or both SMC and SAM. We also evaluated an awareness index (SMC minus SAM). We then tested the interaction between Apolipoprotein E (APOE E4) carrier status and SMC/SAM to evaluate whether the effects were driven by individuals at-risk for AD pathology. Results: In separate models, SMC (-0.081±0.036, p=0.025) and SAM (-0.084±0.278, p=0.003) were both associated with memory decline over approximately six years. However, the AI was not significantly associated with memory decline (0.031±0.024, p=0.19). When both predictors were included in the same model, SAM (-0.074±0.03, p=0.0092) was associated with memory decline, while SMC was not significant (-0.061±0.04, p=0.99). The association between SAM and memory decline was stronger in the APOE E4 carriers than in the non-carriers (APOE-by-SAM interaction: F= 6.07; p= 0.002), and follow up analyses revealed that SAM was particularly predictive of decline only for APOE E4 carriers. The association between SMC and memory decline was independent of APOE E4 carrier status (APOE-by-SMC interaction: F=2.29; p= 0.13). Conclusions: Spouse-appraised memory functioning was more predictive of memory decline than SMC or an awareness index, particularly in APOE E4 carriers, who are at increased risk for AD pathology.